A=s^2 50=S^2 s= sqrt50 s=7.071 ms a^2+a^2=c^2 50+50=c^2 100=c^2 c= sqrt100 c=10ms So the answer would be 10 hope this helped
Answer: -5
Step-by-step explanation: 2 + -11 = -9 and subtract -4 from it since it’s the sum of 2 + -6. -9 - -4 is -9 + 4 so -5
This is because logarithm has its own set of properties that is different from algebra. The term log(3x - 1) is equivalent to log 3x/log 1. If we continue to rearrange and find x, the solution would be:
log(3x - 1) = log28
log 3x/log 1 = log 28
log 3x = log 28 * log 1 = 0
3x = 10⁰ = 1
3x = 1
x = 1/3
<em>So, that means 3x - 1 = 3(1/3) - 1 = 0.</em>
Answer:
The answer is the second one
im sorry if this is wrong
Step-by-step explanation:
Answer:
Step-by-step explanation:
s=rtheta
s/r=theta
11.5/25=theta
theta=.46